Digital litracy in Mexican high school teachers: an analysis of self-perception towards adaptation to change - Tarango, Javier; González-Quiñones, Fidel; Castro-Olivas, Aholibama (Revista General de Información y Documentación, 2024)
The need to achieve sufficient levels of Digital Literacy (DA) in teachers has currently become a priority in educational development, especially in those who participate in training programs with children and adolescents. This research proposal develops an analysis of the self-perception of Mexican teachers in upper secondary education (EMS), who analyze both their condition and that of their students, regarding the capacity for adaptation that can be experienced in the appropriation of new digital knowledge for their application in virtual or face-to-face teaching practice. To achieve this purpose, a descriptive-explanatory research of a mixed (dominantly quantitative) and transectional nature was developed, through the collection of data from 182 teachers in the state of Chihuahua, Mexico, using convenience sampling. The data collection occured through a survey-type instrument, made up of four sections: sociodemographic data, measurement of teaching digital literacy, perceptions towards the processes to the change. The results of the research allowed the identification of a brief conceptual mdodel on AD in teachers, disposition towards lifelong learning in digital issues, forms of manifestation of processes adaptive to change and perceptions towards the present and the future impact of their subjects.